PROTOTYPE MONITORING PENDETEKSI BANJIR MENGGUNAKAN APLIKASI BLYNK BERBASIS ESP32 - Syamsul; Dedy Hendryady; Nurwahid Syam (Institut Teknologi dan Bisnis Bina Adinata, 2023)
This study aims to increase public awareness of floods that are increasingly occurring, flooding is an event or disaster that often occurs due to overflowing river water that exceeds its capacity, causing the surrounding settlements to be flooded which can cause damage and even take lives. The water level in the river is usually confirmed by the community by checking the height directly to ensure the water level does not overflow into the residential area. The research method used is the Prototype model where the workings of this model are very dynamic, efficient, consistent, and more responsive. This prototype is a model whose approach focuses on user needs because user feedback is very basic for developing software. The results of this study indicate that: 1) Prototype flood detection monitoring using the esp32-based blynk application was designed using the HC SR04 ultrasonic sensor, esp32 microcontroller, dfmini player, and speakers and using the blynk application. 2) Implementation of a flood detection monitoring prototype using the esp32-based blynk application can detect water levels properly. Where the warning from the water level level is divided into 3, namely sound 1 with a water level level of 4 - 5 cm is called alert, it can work automatically, sound 2 with a water level level of 6 - 7 cm is called standby and the highest level reaches sound 3, namely 8. – 12 cm is called a hazard and will then appear on the Blynk application according to the height level in the water when it reaches 3 levels of water level.